The Effect of Tax Efficiency, Cash Management, and Investment Policy on the Value of Technology Companies in Bandung - Loso Judijanto (West Science Business and Management, 2024)
This research investigates the impact of tax efficiency, cash management, and investment policy on the value of technology companies in Bandung through a quantitative survey analysis. The study explores the relationships between these financial constructs and firm value, utilizing Structural Equation Modeling with Partial Least Squares (SEM-PLS) on a diverse sample of 170 technology companies. The measurement model analysis demonstrates the reliability and validity of the constructs, while the structural model analysis reveals significant positive correlations between tax efficiency, cash management, investment policy, and firm value. The demographic characteristics of the sample provide context to the findings. The results have practical implications for strategic financial management in the technology sector, emphasizing the importance of tax planning, cash flow optimization, and prudent investment decisions. Despite certain limitations, the study contributes to the existing literature and opens avenues for future research in the dynamic technology landscape of Bandung.